A multifunctional non-viral vector for the delivery of MTH1-targeted CRISPR/Cas9 system for non-small cell lung cancer therapy. (November 2022) - Wang, Yu; Tang, Yan; Zhao, Xiao-mei; Huang, Gui; Gong, Jin-hong; Yang, Shu-di; Li, Hui; Wan, Wen-jun; Jia, Chang-hao; Chen, Gang; Zhang, Xue-nong
Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system adapted from bacteria is a programmable nuclease-based genome editing tool. The long-lasting effect of gene silencing or correction is beneficial in cancer treatment. Considering the need to broaden the practical application of this technology, highly efficient non-viral vectors are urgently required. We prepared a multifunctional non-viral vector that could actively target tumor cells and deliver CRISPR/Cas9 plasmids into nuclei of cancer cells. Protamine sulfate (PS) which contains nuclear localization sequence was utilized to condense plasmid DNA and facilitate nuclei-targeted delivery. Liposome-coated protein/DNA complex avoided the degradation of nuclease in blood circulation. The obtained PS@Lip/pCas9 was further modified with distearoyl phosphoethanolamine-polyethylene glycol-hyaluronic acid (HA) to endow the vector ability to actively target tumor cell. Results suggested that PS@HA-Lip could deliver CRISPR/Cas9 plasmids into nuclei of tumor cells and induce genome editing effect. With the disruption of MTH1 (mutT homolog1) gene, the growth of non-small cell lung cancer was inhibited. Moreover, cell apoptosis in tumor tissue was promoted, and liver metastasis of non-small cell lung cancer (NSCLC) was reduced. Our study has provided a therapeutic strategy targeting MTH1 gene for NSCLC therapy. Statement of significance: CRISPR/Cas9 as a powerful tool for genome editing has drawn much attention. The long-lasting effect possesses unique advantage in cancer treatment. Non-viral vectors have high loading capacity, high safety and low immunogenicity, playing an important role in CRISPR/Cas9 delivery. In our study, a multifunctional non-viral vector for the efficient delivery of CRISPR/Cas9 plasmid was constructed. With the active targeting ligand and nuclei-targeting component, the cargo was efficiently delivered into cell nuclei and exerted genome editing effect. By using this vector, we successfully inhibited the growth and induced the apoptosis of non-small cell lung cancer by disrupting MTH1 expression with good safety. Our work provided an efficient non-vial vector for CRISPR/Cas9 delivery and explored the possibility for cancer treatment. Graphic abstract: Image, graphical abstract